STUDI RONA AWAL LINGKUNGAN PEMBANGUNAN TEMPAT PEMROSESAN AKHIR (TPA) GOHONG KABUPATEN PULANG PISAU - Restu Hikmah Ayu Murti; Sukarmawati, Yuliana; Salam Jawwad, Muhammad Abdus (Al-Ard: Jurnal Teknik Lingkungan, 2022)
The local government of Pulang Pisau, Central Kalimantan plans to build a municipal solid waste landfill located in Gohong Village, Kahayan Hilir District. The Gohong landfill is planned to be built with a sanitary landfill system located in Gohong Village, Kahayan Hilir District, Pulang Pisau Regency with an area of 64,260 m2. Based on this, it is necessary to conduct an initial environmental study of the initial environmental components before planning and development begin, to then be managed and monitored during the activity. This study uses two types of data, which are secondary data and primary data. Secondary data includes topographic data and rainfall at the construction site, while the primary data used is groundwater and river quality, and water biota analysis. The results of the study on the development plan for the Gohong landfill show that this area has a medium category of rainfall. The soil types at the site of the development plan are podsol and alluvial soil types. The quality of river water around the planned development site is class 4 water type with good groundwater quality and has diverse biological components with healthy ecosystems.